DUKUNGAN KELUARGA PASIEN PASCA STROKE SELAMA MENJALANI LATIHAN FISIOTERAPI DI RUMAH SAKIT ROYAL PRIMA MEDAN - Robin Ferdiansyah Sitopu; Yanty Gurning; Teti Mei Wati Ndruru; Siti Nurani Putri Hartati Ndruru; Veronika Sopianti Napitupulu (Universitas Prima Indonesia, 2024)
Busy families mean less support for stroke patients in the recovery period, stroke patients are more adjusted to life after a stroke and grieve the loss of people they know while trying to stay strong to live. This research aims to find out how family support is related to the motivation of post-stroke patients during physical therapy training at RSU Royal Prima Medan in 2024. The research design used in this research is quantitative research with a correlational design because the researcher wants to know the relationship between family support and the patient's level of motivation. stroke in undergoing physiotherapy exercises with a cross sectional approach. The research results found that post-stroke respondents undergoing physiotherapy exercises had good family support and post-stroke respondents undergoing physiotherapy exercises had high motivation. Moreover, there is a relationship between the two variables. Based on the results of statistical tests, it was concluded that there was a difference in proportion (there was a significant relationship) between family support and the motivation of post-stroke patients in undergoing physiotherapy exercises. It is recommended that the community, especially families, be able to provide familysupport to stroke patients, such as the family accompanying the patient in treatment.